Japan's wartime medical atrocities : comparative inquiries in science, history, and ethics - Nie, Jing-Bao, 1962- (London ; New York : Routledge, 2010)
This volume brings together the contributions of a group of scholars from different countries and various academic disciplines. It examines Japan's wartime medical atrocities and their postwar aftermath from a comparative perspective and inquires into perennial issues of historical memory, science, politics, society and ethics elicited by these rebarbative events. The volume's central ethical claim is that the failure to bring justice to bear on the systematic abuse of medical research by Japanese military medical personnel more than six decades ago has had a profoundly retarding influence on the development and practice of medical and social ethics in all of East Asia. The book alsom includes an extensive annotated bibliography selected from relevant publications in Japanese, Chinese and English. --Book Jacket.
Prior to and during the Second World War, the Japanese Army established programs of biological warfare throughout China and elsewhere. In these "factories of death," including the now-infamous Unit 731, Japanese doctors and scientists conducted large numbers of vivisections and experiments on human beings, mostly Chinese nationals. However, as a result of complex historical factors including an American cover-up of the atrocities, Japanese denials, and inadequate responses from successive Chinese governments, justice has never been fully served. --
Introduction: Medical atrocities, history and ethics / Arthur Kleinman, Jing-Bao Nie, and Mark Selden -- Unit 731 and the Japanese Imperial Army's biological warfare program / Tsuneishi Keiichi -- Medicine-related war crimes trials and post-war politics and ethics : the unresolved case of Unit 731, Japan's bio-warfare program / Suzy Wang -- Research on humans at the Khabarovsk War Crimes Trial : a historical and ethical examination / Boris G. Yudin -- Data generated in Japan's biowarfare experiments on human victims in China, 1932-1945, and the ethics of using them / Till Bärnighausen -- Discovering traces of humanity : taking individual responsibility for medical atrocities / Nanyan Guo -- On the altar of nationalism and the nation-state : Japan's wartime medical atrocities, the American cover-up, and postwar Chinese responses / Jing-Bao Nie -- Bioethics and exceptionalism : a German example of learning from "medical" atrocities / Ole Döring -- Racial hygienist Otmar von Vershuer, the Confessing Church, and comparative reflections on postwar rehabilitation / Peter Degen -- America's memory problems : diaspora groups, civil society and the perils of "chosen amnesia" / David B. MacDonald -- Japanese and American war atrocities, historical memory, and reconciliation : the Asia-Pacific War to today / Mark Selden -- Annotated bibliography : primary sources and secondary literature in Japanese, Chinese and English / Nanyan Guo and Jing-Bao Nie -- Appendix A: The experiments conducted under the Third Reich and Imperial Japan and postwar use of such data / Suzy Wang -- Appendix B: The experiments conducted under the US government / Suzy Wang.
Includes bibliographical references (p. 207-230) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Japan. -- Rikugun. -- Kantōgun. -- Butai, Dai 731.; World War, 1939-1945 -- Atrocities -- Japan; World War, 1939-1945 -- Biological warfare -- Japan; World War, 1939-1945 -- Atrocities -- China; Human experimentation in medicine -- Japan -- History -- 20th century; Human experimentation in medicine -- Moral and ethical aspects; War crimes -- History -- 20th century; War crime trials -- History -- 20th century; War Crimes -- history -- Japan; War Crimes -- history -- China; Human Experimentation -- ethics -- Japan; Human Experimentation -- ethics -- China; Biological Warfare -- history -- China; Biological Warfare -- history -- Japan; History, 20th Century -- China; History, 20th Century -- Japan; World War II -- China; World War II -- Japan; Electronic books